PENGARUH TINGKAT SUKU BUNGA, PENDAPATAN, TINGKAT INFLASI DAN TINGKAT PENDIDIKAN TERHADAP TABUNGAN MASYARAKAT KOTA PADANG - Fitri, Yulia; . Ansofino, Dr.; Ramayani, S.Pd,ME, Citra (Pendidikan Ekonomi, 2014)
Â ABSTRACTIndicators used in this research is to know the condition of peopleâs to saving Padang city. Purpose of this study was to thetermine the effect of interest rates, income, and education level of the inflation rate and shimultaneous partial to public savings Padang city. Collecting date that relates to public savings, interest rates, income, inflation rate and the level of education the was optained from the central statistical agencies and bodyes of local financial economic statistics Indonesian banks. This study used multiple linear regression analysis hypothesis thest to examine the effect of partiyalli using the t test and simultaneous testing bedween the independent variables on the dependent variable can then be used with the Eftest the results showed that ther is an effect partially significantly and some have no effect. While simultaneously interest rates, income, inflation rate and the level of education jointly affect private savings Padang city.